2018
DOI: 10.1016/j.dcn.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of social and non-social cues to direction in adults with autism spectrum disorder and neurotypical adults with autistic traits

Abstract: HighlightsAutistic traits negatively predict adaptation magnitude for social and non-social cues.Only adaptation magnitude for social eye-gaze is diminished in adults with ASD.High ADOS scores predict smaller aftereffects for head and eye-gaze direction.Diminished adaptation in autistic adults may only affect impaired perceptual domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 64 publications
1
45
6
Order By: Relevance
“…In this study, we compared autistic and typical participants, of similar age and ability, on the adaptive coding of the speed of biological motion. We hypothesised that autistic individuals' atypicalities in the adaptive coding of facial stimuli (Ewing et al 2013a;Lawson et al 2018;Pellicano et al 2013;Rhodes et al 2018;Rutherford et al 2012) should generalise to non-facial social stimuli and predicted that autistic participants should show less adaptation to the speed of the PLDs of our task than the typical comparison participants. We found that both groups showed significant adaptation effects-but, contrary to our prediction, that the magnitude of adaptation was comparable in autistic and typical participants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we compared autistic and typical participants, of similar age and ability, on the adaptive coding of the speed of biological motion. We hypothesised that autistic individuals' atypicalities in the adaptive coding of facial stimuli (Ewing et al 2013a;Lawson et al 2018;Pellicano et al 2013;Rhodes et al 2018;Rutherford et al 2012) should generalise to non-facial social stimuli and predicted that autistic participants should show less adaptation to the speed of the PLDs of our task than the typical comparison participants. We found that both groups showed significant adaptation effects-but, contrary to our prediction, that the magnitude of adaptation was comparable in autistic and typical participants.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus also very important to control for attention in adaptation studies (see also gaze-contingent paradigms; e.g., Wilms et al 2010). To our knowledge, controlling for attention has been employed in earlier studies on adaptation in autism by Ewing et al (2013b) on face identity, Karaminis et al (2015) on perceptual causality, Lawson et al (2018) on eye-gaze direction and Rhodes et al (2018) on facial expression. Our study on adaptation to the running speed of biological motion in autism is novel in combining the use of a secondary attention task with eye-tracking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations